Teachers’ Perception Toward the Use of Zoom for English Learning at Junior High School of Tellu Limpoe Sidrap - Dewi, Dewi Isrianti (IAIN Parepare, 2023)
Abstract The objective of this research were: to analyze the teachers’perception on using zoom and to analyze the teachers’reaction toward the use of zoom for English learning at junior high school of tellu limpoe Sidrap. This research used descriptive qualitative. Creswell (2013) noted that descriptive qualitative was about understanding and perspective. The subject of this research were 10 english teachers from 3 juniour high school of Tellu Limpoe Sidrap. This research applied interview guidance. It found that Teachers’perception were the zoom application made easier,fun,help the teacher in teaching English. The zoom application influenced the learning process in school,the zoom application influenced enough English skill of learners, and the zoom application made easy to use in learning English. The teachers’reaction were techers though the zoom application was recommended to use if the teachers cannot go to school for teaching,they can teach in the home,because zoom application gave more the advantages than disadvantages,the teachers supposed that bad network was the disadvantagesof zoom application,the zoom’s problems were bad net work and wastafel quota, and the last zoom application had completely item or features to use in teaching process that make easier for teacher and student. Keyword : Zoom, Perception, Reaction, English Teacher, Learning Process from Home.